2021
DOI: 10.3390/ijerph18126534
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Perspective towards E-Exams during COVID-19 Outbreak: Evidence from Higher Educational Institutions of India and Saudi Arabia

Abstract: Online examinations, commonly referred to as e-exams (electronic examinations), underwent a considerable progression, getting adapted ubiquitously among higher education institutions worldwide. Their preferment was rapid due to the emergence of the COVID-19 pandemic. The process of conducting exams online is being opted as the appropriate way of assessment, ensuring the students’ safety and well-being. According to Warts et al., this form of examination has been pretty effective in the past when blended with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Their preference was rapid due to the emergence of the COVID-19 pandemic. The online examination process is being adopted as the appropriate way of evaluating, while ensuring the safety and well-being of students [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their preference was rapid due to the emergence of the COVID-19 pandemic. The online examination process is being adopted as the appropriate way of evaluating, while ensuring the safety and well-being of students [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the development of e-technology and better internet networks, the whole platform has changed from an onsite to online learning mode [ 16 ]. On top of the different electronic media such as television, satellite, and CD-ROM, e-learning is classified in the following way: “education delivered via internet”, and virtual learning is referred to as “education delivered only via the internet or web-based media” by some experts [ 17 ]. E-learning is stated as “bridging the space between teachers and students through the use of web-based technology” [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the increase use of massive online open courses and online degrees for reaching out to learners throughout the globe (Palvia et al, 2018) has raised the obvious need for reliable remote assessment methods in order to maintain the students' flexibility to be tested from anywhere without having to commute to campus. This adds to other notable advantages of online assessments including reduction of paper usage, decreased concerns over the security of transporting test papers, flexible venue, random selection and reproducibility of exam questions, and the overall efficiency concerning the time, effort, and expenditure on conducting the examination (Andreou et al, 2021; Betlej, 2013; Khan et al, 2021; Rogers, 2006; Spivey & McMillan, 2014).…”
Section: Remote Proctoringmentioning
confidence: 99%
“…Another concern is related to the need of adequate testing environment (e.g., consistent Wi‐Fi, quiet surroundings) and the incompetency of the student's technological skills, which requires adding a back‐up method in case of unexpected problems (Ahmed et al, 2021; Gonzales et al, 2020). Moreover, research has shown that these hurdles in technological settings and skills, in addition to the reduced personalized engagement with faculty, have contributed to increased psychological stress to both instructors and students (Spivey & McMillan, 2014), resulting in negative influence on students' performance and grades (Khan et al, 2021). Bisht et al (2020), who surveyed students at a university in India, found that the online assessment is quite acceptable among students with some concerns, pertaining to technical issues—such as Internet connectivity—and financial constraints, that is, with respect to purchasing laptops or other devices.…”
Section: Remote Proctoringmentioning
confidence: 99%
See 1 more Smart Citation